The Unravelling Paediatric Stroke: A Rare Presentation of Paediatric Moya Moya Disease with Simultaneous Involvement of Anterior and Posterior Circulation - Debleena Pal; Srijita Mandal; Uddalok Das; Usashi Bannerjee; Ivy Banerjee (Swiss Journal of Radiology and Nuclear Medicine, 2025)
Moya Moya disease is a rare cerebrovascular disorder characterized by progressive stenosis of the internal carotid arteries and their branches, leading to a range of neurological symptoms. This case report discusses a 14-year-old boy presenting with classic symptoms associated with Moya Moya disease. The diagnostic process involved imaging studies, which confirmed the characteristic findings of the disease along with a specific ANA study which further helped in excluding the association of any other autoimmune disease. Treatment options were explored, including, the use of therapeutic drugs like Aspirin and some statins, aimed at preventing TIAs and alleviating symptoms. This case highlights the importance of early recognition and management of Moya Moya disease to prevent serious neurological deficits and improve the quality of life in affected children and adolescents. Further research is needed to explore the long-term outcomes of various treatment strategies for this challenging condition.